Thoracic wall malignant hemangiopericytoma. - Perrier, José; Somma, Caren; Bergalli, Luis; Rinaldi, Bruno (Cirugía del Uruguay, 1985)
Primitiva tumors in the thóracic wall are exceptional. The arise diagnostic problems that in most cases must be met through extemporaneous biopsy or the histologic study by inclusion in paraffin. Authors present a case of malignan! hemangiope• ricytoma in !he thoracic wall. The solution was complete resection of same plus ihe thoracic wall adjacent to the area where it was set and closing of the opening with Marlex mesh. No other treatment was administered.